Pedagogical conditions for forming emotional culture of future primary school teachers through fine arts (Pedagogy of Higher and Secondary Education, 2014)
Stas T. V. Pedagogical conditions for forming emotional culture of future primary school teachers through fine arts.The article outlines the pedagogical conditions for forming emotional culture of future primary school teachers through fine arts: providing emotional and volitional regulation of learning activity; applying creative projects as a part of emotional feedback; performing educational and creative tasks, interactive methods and techniques, active forms of practice at fine arts classes; enhancing emotional aspects of teaching fine arts.
Keywords: pedagogical conditions; future primaty school teacher; empathy; project projecting; interactive methods